Diphenhydramine as a selective probe to study H+-antiporter function at the blood–brain barrier: Application to [11C]diphenhydramine positron emission tomography imaging. Issue 6 (June 2017) - Auvity, Sylvain; Chapy, Hélène; Goutal, Sébastien; Caillé, Fabien; Hosten, Benoit; Smirnova, Maria; Declèves, Xavier; Tournier, Nicolas; Cisternino, Salvatore
Diphenhydramine, a sedative histamine H1 -receptor (H1 R) antagonist, was evaluated as a probe to measure drug/H + -antiporter function at the blood–brain barrier. In situ brain perfusion experiments in mice and rats showed that diphenhydramine transport at the blood–brain barrier was saturable, following Michaelis–Menten kinetics with a Km  = 2.99 mM and Vmax  = 179.5 nmol s −1  g −1 . In the pharmacological plasma concentration range the carrier-mediated component accounted for 77% of diphenhydramine influx while passive diffusion accounted for only 23%. [ 14 C]Diphenhydramine blood–brain barrier transport was proton and clonidine sensitive but was influenced by neither tetraethylammonium, a MATE1 (SLC47A1), and OCT/OCTN (SLC22A1-5) modulator, nor P-gp/Bcrp (ABCB1a/1b /ABCG2) deficiency. Brain and plasma kinetics of [ 11 C]diphenhydramine were measured by positron emission tomography imaging in rats. [ 11 C]Diphenhydramine kinetics in different brain regions were not influenced by displacement with 1 mg kg −1 unlabeled diphenhydramine, indicating the specificity of the brain positron emission tomography signal for blood–brain barrier transport activity over binding to any central nervous system target in vivo. [ 11 C]Diphenhydramine radiometabolites were not detected in the brain 15 min after injection, allowing for the reliable calculation of [ 11 C]diphenhydramine brain uptake clearance (Clup  = 0.99 ± 0.18 mL min −1  cm −3 ). Diphenhydramine is a selective and specific H + -antiporter substrate. [ 11 C]Diphenhydramine positron emission tomography imaging offers a reliable and noninvasive method to evaluate H + -antiporter function at the blood–brain barrier.